Some Empirical Evidence on the Decreasing Scale Elasticity - Ringstad, Vidar (Econometrica, 1974)
[In the theory of production it is frequently assumed that the scale elasticity is decreasing with scale. There are, however, very few empirical studies that provide support for this assumption. The results of this study, based on individual establishment data, suggest quite clearly that the scale elasticity is decreasing with scale in Norwegian mining and manufacturing.]